The Choices of Young Europeans in the Post-Crisis Reality - Proposal of an AHP - Based Decision - Making Model - Gawlik, Remigiusz (Studia Oeconomica Posnaniensia, 2017)
The paper proposes a decision-making model that would allow young Europeans to make conscious choices in the early stages of their professional and private life. The motivation for such a study comes from the lack of feeling of stability between young people that can be perceived as one of the repercussions of the last global financial crisis. A decision-making model based on the Analytic Hierarchy Process method has been proposed. Decision-makers are young people who are on the verge of their adult lives. The subject of the decision-making is such a ranking of determinants of quality of life that would provide individuals with the highest level of life satisfaction in the future. The analysis embodies material (quantitative) and non-material (qualitative) determinants of decision-making. After application of the presented model young people could make more conscious choices, consonant with their hierarchy of values, needs and individual expectations. As a result, the economy will obtain more motivated employees, whereas society has less frustrated and happier citizens.